Investigation on the critical parameters affecting the working design dynamics of a torque motor employed in an electro-hydraulic servovalve. (January 2019) - A S, Sharan; Hiremath, Somashekhar S; Venkatesha, C S; Karunanidhi, S
The torque motor is an intricate assembly in electro-hydraulic technology and plays a crucial role in converting the electrical signal into controlled mechanical output signal. It involves many precise components, such as the feedback spring, armature and its coil, permanent magnet, feed pipe, flexure shaft, jetpipe, and flexure support. The components are embedded together as a single operating component. Each component contributes to the effective dynamics of the system. The present paper proposes a novel approach to investigate the effect of critical parameters on the working design dynamics of the torque motor employed in the jetpipe electro-hydraulic servovalve. Based on the principles of mechatronics, a mathematical model is developed. The model-based design approach is employed to investigate the dynamics of the system. The required simulation parameters of the critical and precision components were obtained from solid and finite element (FE) models. The solid and FE models of the critical and precision components were first analyzed with suitable boundary and loading conditions to establish the stiffness. To validate the obtained FE results, experiments were carried out with a specially designed and fabricated test set-up. Based on the basic principle of electromagnetics, a nonlinear FE model of torque motor is analyzed for magnetic field distribution, the torque developed, and armature and jetpipe deflection for varied input current. From the results obtained, good agreement was observed between FE, simulated, and experimental values. The present novel approach enables one to improve the working design dynamics of the torque motor.